98 - A VALUE OF A HUMANIZED NURSERING CARE TO PRETERM NEWBORN INTERNED IN NEWBORN INTENSIVE CARE UNITY (Fiep Bulletin - online, 2011)
The preterm newborn needs cares in Newborn Intensive Care Unity (NICU), environment that exposes to highly stimulant sensorial and environmental factors. So, this exploratory study, developed through a bibliographic research aims to develop a character moral theoretic reflection about a nursing proper conduct that reveling itself as a care, makes easy the preterm newborn's adaptation to a NICU, without depriving of the necessary assistance to its health and maintenance of its life. It is concluded that a nurse intervention measures must reveal, if not emerging from its ontological essence, but, of an ethical conscience, his way of "be-care", and simultaneously, his way of "be-work" and, in a safety and humanized way, favor the reestablishment of preterm newborn interned in NICU.
Keywords: Pre-term Newborn; Newborn Intensive Care Unities (NICU); care; nursing; moral and ethics